Intraoperative augmented reality fiber tractography complements cortical and subcortical mapping - Swathi Chidambaram; Diana Anthony; Tatiana Jansen; Vera Vigo; Juan C. Fernandez Miranda (World Neurosurgery: X, 2023)
Augmented reality (AR) has been found to be advantageous in enhancing visualization of complex neuroanatomy intraoperatively and in neurosurgical education. Another key tool that allows neurosurgeons to have enhanced visualization, namely of white matter tracts, is diffusion tensor imaging (DTI) that is processed with high-definition fiber tractography (HDFT). There remains an enduring challenge in the structural–functional correlation of white matter tracts that centers on the difficulty in clearly assigning function to any given fiber tract when evaluating them through separated as opposed to integrated modalities. Combining the technologies of AR with fiber tractography shows promise in helping to fill in this gap between structural–functional correlation of white matter tracts. This novel study demonstrates through a series of three cases of awake craniotomies for glioma resections a technique that allows the first and most direct evidence of fiber tract stimulation and assignment of function or deficit in vivo through the intraoperative, real-time fusion of electrical cortical stimulation, AR, and HDFT. This novel technique has qualitatively shown to be helpful in guiding intraoperative decision making on extent of resection of gliomas. Future studies could focus on larger, prospective cohorts of glioma patients who undergo this methodology and further correlate the post-operative imaging results to patient functional outcomes.